2022
DOI: 10.1371/journal.pone.0266504
|View full text |Cite
|
Sign up to set email alerts
|

Exploring experiences and impact of the COVID-19 pandemic on young racially minoritised people in the United Kingdom: A qualitative study

Abstract: Within high-income-countries, the COVID-19 pandemic has disproportionately impacted people from racially minoritised backgrounds. There has been significant research interrogating the disparate impact of the virus, and recently, interest in the long-term implications of the global crisis on young people’s mental health and wellbeing. However, less work explores the experiences of young people from racialised backgrounds as they navigate the pandemic, and the specific consequences this has for their mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 45 publications
(39 reference statements)
2
27
0
Order By: Relevance
“…48 Ever-changing public health recommendations and policies—based on a constantly evolving pandemic—appeared to cause confusion and anxiety (exacerbated by social media) and enabled mistrust of government, scientists, and public health officials to flourish. 49 Misinformation and mistrust also contributed to heterogeneity in vaccine uptake across countries. For example, vaccine hesitancy and low uptake in Zambia was affected by myths and misinformation about COVID-19 and related vaccines, fear of adverse side-effects, and concern about vaccine efficacy.…”
Section: Lesson 2: Create An Enabling Environmentmentioning
confidence: 99%
“…48 Ever-changing public health recommendations and policies—based on a constantly evolving pandemic—appeared to cause confusion and anxiety (exacerbated by social media) and enabled mistrust of government, scientists, and public health officials to flourish. 49 Misinformation and mistrust also contributed to heterogeneity in vaccine uptake across countries. For example, vaccine hesitancy and low uptake in Zambia was affected by myths and misinformation about COVID-19 and related vaccines, fear of adverse side-effects, and concern about vaccine efficacy.…”
Section: Lesson 2: Create An Enabling Environmentmentioning
confidence: 99%
“…Below we summarise findings from four qualitative studies (15)(16)(17)(18). The research cited above adds to the evidence base that decontextualized approaches to mental health treatment make little sense to people whose psychological distress is linked with ongoing adversity.…”
Section: Supply or Demand?mentioning
confidence: 99%
“…The context of the COVID-19 pandemic also reduced opportunities related to job search and availability of work for young adults during a critical life stage of entry into the labour market ( OECD, 2021c ). Qualitative explorations have indicated that these economic disruptions represented major concerns for young adults who reported increasing feelings of precarity, financial strain, and uncertainty about their career development ( Burgess et al, 2022 ; Lindsay & Ahmed, 2021 ). These experiences of emotional stress due to the COVID-19-induced economic crisis represent critical risk factors for mental health challenges ( Achdut & Refaeli, 2020 ; de Miquel et al, 2022 ; Graupensperger et al, 2022 ; Ranta et al, 2020 ; Shanahan et al, 2022 ), including depression, the prevalence of which has steadily increased among young adults in recent decades ( Mojtabai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%